تبثیر یک ديرٌ تمریه اصالحی بب ي بذين رَبسبزی مبیًفبضیبل بر میسان درد، پبسچر، ضبخص وبتًاوی ي کیفیت زوذگی مردان مبتال بٍ سىذريم ومبیطگر يیذئًیی. - سیذ مجتبی ضریعت پ وبصر محمذ رحیمی; رضب امیه زادٌ (Journal of Safety Promotion & Injury Prevention, 2022)
Background and Aim: The aim of this study was to investigate the effect of a correctional exercise course with myofascial release on pain, posture, disability index and quality of life in people with video display syndrome. Methods: This study was semi-experimental and applied with a pre-test-post-test design with a control group. 45 middle-aged men (40-45 years old) suffering from video screen syndrome based on the study inclusion criteria were selected as a statistical sample and randomly divided into three experimental groups 1 (15 people), experimental 2 (15 people) and control (15 people) were divided. Before and after 6 weeks of training intervention that took place for 45 minutes and 3 sessions per week; In order to measure the amount of pain and disability, forward head posture, kyphosis and quality of life, respectively, using visual analog scale (VAS), neck disability index questionnaire (NDI), neck pain and disability scale questionnaire (NPDS), photography method and SF-36 questionnaire were used. Results: The results showed that the amount of pain (F=31.40 and P=0.001), forward head posture (F=29.75 and P=0.01), kyphosis (F=21.94 and P=0.01) P), disability index (F=30.79 and P=0.01) and quality of life (F=51.83 and P=0.01) of the intervention group improved significantly in the post-test compared to the pre-test (P <0.05). Also, a significant difference was observed in all the variables between the experimental 1 and experimental 2 groups in the post-test (P<0.05). So that corrective exercises with myofascial release had a greater effect on the improvement of research variables. Conclusion: The findings showed a reduction in pain, improved posture, disability index and quality of life in the group of corrective exercises with myofascial release compared to the group of corrective exercises without myofascial release; Therefore, in order to reduce musculoskeletal injuries and increase efficiency and productivity, it is recommended to use corrective exercises with myofascial release for men with video monitor syndrome.